2007
DOI: 10.1080/14735903.2007.9684831
|View full text |Cite
|
Sign up to set email alerts
|

Rural poverty in Mexico: assets and livelihood strategies among the Mayas of Yucatán

Abstract: Understanding poverty and sustainability needs livelihood studies that acknowledge heterogeneity at the community and household level. This is particularly true for Latin America where inequality and ethnicity are important aspects of poverty and sustainability. This paper is a detailed examination of the natural resources, socio-economic assets and livelihood strategies of two Mayan communities of the Mexican State of Yucatán. There were three fundamental objectives: to elucidate the people's perceptions of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 27 publications
1
10
0
1
Order By: Relevance
“…Similar results were reported in Kenya where the poor depend mostly on risky and less rewarding employments (such as charcoal making and fire wood selling) while the better off diversified into higher return off-farm activities such as salaried employment Freeman et al 2004;Liyama et al 2008). Lack of skills, knowledge, and financial capital are key barriers for the poor to engage in high economic return activities (Poole et al 2007;Babulo et al 2008;Liyama et al 2008). The finding was consistent with studies conducted in Kenya that showed the lowest third income groups were short of key assets except for their family working labour Ellis and Freeman 2004).…”
Section: Livelihood Diversification Strategy-poverty Linkssupporting
confidence: 79%
See 4 more Smart Citations
“…Similar results were reported in Kenya where the poor depend mostly on risky and less rewarding employments (such as charcoal making and fire wood selling) while the better off diversified into higher return off-farm activities such as salaried employment Freeman et al 2004;Liyama et al 2008). Lack of skills, knowledge, and financial capital are key barriers for the poor to engage in high economic return activities (Poole et al 2007;Babulo et al 2008;Liyama et al 2008). The finding was consistent with studies conducted in Kenya that showed the lowest third income groups were short of key assets except for their family working labour Ellis and Freeman 2004).…”
Section: Livelihood Diversification Strategy-poverty Linkssupporting
confidence: 79%
“…DfID 1999;Scoones 2005;Shiferaw et al 2007). Many cases that show links between poverty, livelihood, and sustainability largely depend on location-specific conditions and farmer characteristics (Poole et al 2007;Okello et al 2009). This requires empowerment, inclusion, and socio-economic and sustainable development policies with relevance to marginalized communities (Poole et al 2007).…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations